Clinical evaluation of [18F]pitavastatin for quantitative analysis of hepatobiliary transporter activity. (June 2022) - Nakaoka, Takayoshi; Kaneko, Ken-ichi; Irie, Satsuki; Mawatari, Aya; Igesaka, Ami; Uetake, Yuta; Ochiai, Hidenori; Niwa, Takashi; Yamano, Emi; Wada, Yasuhiro; Tanaka, Masaaki; Kotani, Kohei; et al.
Abstract: It is widely accepted that uptake and efflux transporters on clearance organs play crucial roles in drug disposition. Although in vitro transporter assay system can identify the intrinsic properties of the target transporters, it is not so easy to precisely predict in vivo pharmacokinetic parameters from in vitro data. Positron emission tomography (PET) imaging is a useful tool to directly assess the activity of drug transporters in humans. We recently developed a practical synthetic method for fluorine-18-labeled pitavastatin ([ 18 F]PTV) as a PET probe for quantitative evaluation of hepatobiliary transport. In the present study, we conducted clinical PET imaging with [ 18 F]PTV and compared the pharmacokinetic properties of the probe for healthy subjects with or without rifampicin pretreatment. Rifampicin pretreatment significantly suppressed the hepatic maximum concentration and biliary excretion of the probe to 52% and 34% of the control values, respectively. Rifampicin treatment markedly decreased hepatic uptake clearance (21% of the control), and moderately canalicular efflux clearance with regard to hepatic concentration (52% of the control). These results demonstrate that [ 18 F]PTV is a useful probe for clinical investigation of the activities of hepatobiliary uptake/efflux transporters in humans.